Scavenging of small bird carrion in southwestern Germany by beetles, birds and mammals - Henrich, Maik; Tietze, Dieter Thomas; Wink, Michael (Journal of ornithology, 2017)
When considering the impact of wind turbines on the mortality of birds and bats, it is important to know the length of time that a carcass will be detectable. Thousands of small animals (such as many passerine birds with high mortality rates) die every day, but dead animals are rarely found by casual observers in the field. What is the fate of small carcasses in European ecosystems? During this project, we placed 120 defrosted day-old chicks (Gallus gallus f. domestica) as a model for a small carcass in a variety of habitats in southwestern Germany between the end of May and the beginning of December 2014. Using automatic trail cameras, we recorded the scavengers which visited the carrion or were feeding on it. Overall, two-thirds of the carcasses were removed under these conditions within a 5-day period. During the summer months, 20 % of the chicks were buried by burying beetles (Nicrophorus sp.), and 40 % were removed by nine mammal and three bird species. The most important vertebrate scavengers were the Red Fox (Vulpes vulpes), the Common Buzzard (Buteo buteo), the European Magpie (Pica pica) and the Domestic Cat (Felis catus). Among the scavenged chicks, 38.8 % vanished during the first 24 h of exposure. The median persistence time was 2.79 days. Persistence times were not dependent on habitat type, but carrion persisted longer on average in autumn than in summer. Knowledge of the factors influencing carcass persistence is important for estimating mortality in songbirds or bats in the context of wind turbines.
Published online 18 June 2016
Gesehen am 17.03.2017